ENZYMATIC SACCHARIFICATION OF HYDROGEN PEROXIDE PRETREATED OF RICE STRAWFOR BIOETHANOL PRODUCTION - Thi Minh Nguyet, Nguyen; Dinh Cuong, Thai (Journal of Forestry Science and Technology, 2016)
Rice straw contains more than 35% of cellulose.This material presents a potential feedstock for bioethanol production. In this study, the two-stage pretreatment of Q5 specie rice straw was used for preparation of cellulosic pulp for enzymatic saccharification. Firstly, rice straw was treated by mixture of hydrogen peroxide with sulfuric acid and sodium molipdate in conditions of liquor-to rice straw ratio (10:1) ml/g, temperature 120oC and 120 mins of cooking. Secondary, pretreated rice straw was submerged in sodium hydroxide solution (2.5% w/w), at temparature of 100oC, for 30 min. Enzymatic saccharification of pretreated rice straw by Novozymes commercial enzyme Cellic®CTec2 and Cellic®HTec2 with dosage of 80 FPU/g and 18 FPU/g of pretreatred rice straw achieved the reduce sugar yield an average 40.0% - 41.0% of over dry rice straw. Fermentation of sugars has been succesful.